2016
DOI: 10.1007/s40263-016-0399-3
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT6 Receptor Antagonists in Alzheimer’s Disease: Therapeutic Rationale and Current Development Status

Abstract: Alzheimer's disease (AD) is the most common cause of dementia in elderly people. Because of the lack of effective treatments for this illness, research focused on identifying compounds that restore cognition and functional impairments in patients with AD is a very active field. Since its discovery in 1993, the serotonin 5-HT receptor has received increasing attention, and a growing number of studies supported 5-HT receptor antagonism as a target for improving cognitive dysfunction in AD. This article reviews t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 103 publications
0
57
0
Order By: Relevance
“…This derivative at doses of 1 and 3 mg/kg enhanced short-term memory and improved cognitive flexibility in rats [80]. Although Phase II trials have not yet been concluded [81,82], this drug candidate could be useful in treating dementia in AD [83]. Another selective antagonist, AVN-322, which is a derivative of AVN-101 and AVN-211, is undergoing Phase I trials for AD and schizophrenia.…”
Section: -Ht Receptorsmentioning
confidence: 99%
“…This derivative at doses of 1 and 3 mg/kg enhanced short-term memory and improved cognitive flexibility in rats [80]. Although Phase II trials have not yet been concluded [81,82], this drug candidate could be useful in treating dementia in AD [83]. Another selective antagonist, AVN-322, which is a derivative of AVN-101 and AVN-211, is undergoing Phase I trials for AD and schizophrenia.…”
Section: -Ht Receptorsmentioning
confidence: 99%
“…The procognitive properties of antagonists of the 5-HT 6 receptor have since been well-documented in preclinical animal models (Mitchell and Neumaier, 2005; Fone, 2008; Arnt et al, 2010; Meneses et al, 2011) that have also suggested a potential benefit of combining a 5-HT 6 receptor antagonist with an AChEI, as 5-HT 6 receptor antagonism was shown to potentiate the neurochemical, electrophysiological, and procognitive effects of the AChEI donepezil (Marcos et al, 2008; Dawson, 2011; de Bruin et al, 2011). Several 5-HT 6 receptor antagonists have now entered clinical development for the treatment of AD (Maher-Edwards et al, 2011; Wilkinson and Windfeld, 2014; Calhoun et al, 2017; Ferrero et al, 2017). Of these, idalopirdine (Lu AE58054), a high affinity ( Ki = 0.83 nm) and selective 5-HT 6 receptor antagonist (Arnt et al, 2010), is furthest advanced, and in phase III development for the treatment of mild to moderate AD as an adjunct therapy to AChEIs.…”
Section: Introductionmentioning
confidence: 99%
“…Given that some of the potential indications, such as cognitive impairment in Alzheimer disease and age-related cognitive decline, are related to advancing age, it is important to understand the effects of age on 5-HT 6 receptors and to ascertain whether they remain an important target in older age groups. This importance is further underscored by recent negative results from 2 phase III trials of the 5-HT 6 antagonist idalopirdine for cognitive impairment in Alzheimer disease, despite promising results in preclinical studies (16).…”
mentioning
confidence: 99%